Interesses econômicos, representação política e produção legislativa no Brasil sob a ótica do financiamento de campanhas eleitorais - Bruno Carazza dos Santos (2016)
This thesis analyses the financing of the Brazilian elections and the rules governing its Presidential system, showing how they favor special interest groups at the expense of the whole society. Collected and processed data indicates that a growing volume of donations from relatively few and large donors mainly corporates have influenced the results of the Brazilian elections, usually motivated by interests in government action. This economic influence extends to the legal and institutional framework that governs the relationship between the Executive and Legislative branches, creating great opportunities for rent seeking behavior in the legislative process. The thesis concludes that the recent decision of prohibiting the electoral donations from corporations by the Brazilian Supreme Court is inefficient to curb the economic influence in the elections and the policy capture by special interest groups. In order to deal with these problems, this thesis presents several proposals for addressing this issue more broadly, taking into account both the demand and supply of campaign financing, as well as combating the rent seeking behavior in the political system and in the Brazilian legislative process.